Review article: Flavonoid Extraction Method of Parsley Leaf Extract (Petroselinum crispum) - Yogi Maha Putra, I Made Artadinatha; Kusuma Dewi, Luh Putu Mirah (Journal of Food and Pharmaceutical Sciences, 2025)
Flavonoids are bioactive polyphenolic compounds known for their antioxidant, anti-inflammatory, and antimicrobial properties. Although widely distributed in plants, parsley (Petroselinum crispum) is highlighted for its high flavonoid content, which is recognized as the dominant class of secondary metabolites compared to other constituents such as essential oils and pigments, making it a strong candidate for pharmaceutical applications. This review aimed to evaluate and compare various extraction methods used to isolate flavonoids from parsley leaves. A systematic literature search was conducted through Google Scholar, Scopus, and PubMed for articles published between 2014 and 2024 using keywords “flavonoid,” “parsley leaves,” and “extraction method.” Inclusion criteria comprised full-text original articles in English or Indonesian reporting extraction methods and total flavonoid content; reviews and incomplete studies were excluded. Among the methods reviewed, Ultrasonic-Assisted Extraction (UAE) proved most effective. When normalized to 1 g/minute, UAE yielded 0.312 mg/g of total flavonoids, demonstrating higher efficiency in terms of extraction yield and time. UAE utilizes acoustic cavitation to enhance solvent penetration and mass transfer, improving yield while preserving compound integrity. Ethanol was identified as the optimal solvent due to its polarity and compatibility with flavonoid structures. In conclusion, UAE with ethanol presents a promising strategy for efficient flavonoid extraction from parsley in pharmaceutical and nutraceutical applications.